Low Immune Activation in Early Pregnancy Is Associated With Preterm But Not Small-for-gestational-age Delivery in Women Infected With Human Immunodeficiency Virus Initiating Antiretroviral Therapy in Pregnancy: A Prematurity Immunology in HIV-infected Mothers and their Infants Study (PIMS) Case-control Study in Cape Town, South Africa. (19th February 2021) - Mdletshe, Nontlantla; Thobakgale, Christina; Malaba, Thokozile R; Madlala, Hlengiwe; Myer, Landon; Muema, Daniel M; Mogeni, Polycarp; Gray, Clive M; Altfeld, Marcus; Newell, Marie-Louise; Ndung'u, Thumbi
Abstract: Background: Mechanisms underlying an association between human immunodeficiency virus (HIV) or antiretroviral therapy (ART) during pregnancy with risk of preterm delivery (PTD) and small-for-gestational-age (SGA) remain unclear. We explored the association between cellular immune activation and PTD or SGA in women with HIV initiating ART during or before pregnancy. Methods: Women with HIV enrolled at median 15 weeks' gestation, were analyzed for immune markers, and matched on ART initiation timing (15 women initiated pre- and 15 during pregnancy). There were 30 PTD (delivery <37 weeks), 30 SGA (weight for age ≤10th percentile) cases, and 30 controls (term, weight for gestational age >25th percentile) as outcomes. Lymphocytes, monocytes, and dendritic cell populations and their activation status or functionality were enumerated by flow cytometry. Results: PTD cases initiating ART in pregnancy showed decreased CD8 + T cell, monocyte, and dendritic cell activation; increased classical (CD14 + CD16 – ) and intermediate (CD14 + CD16 + ) monocyte frequencies; and decreased inflammatory monocytes (CD14 dim CD16 + ) compared with SGA cases and term controls (all P  < .05). Allowing for baseline viral load, the immune markers remained significantly associated with PTD but only in women initiating ART in pregnancy. Lower monocyte activation was predictive of PTD. TLR ligand-induced interferon-α and macrophage inflammatory protein-1β levels in monocytes were significantly lower in PTD women initiating ART in pregnancy. Conclusion: Low immune activation, skewing toward anti-inflammatory monocytes, and lower monocyte cytokine production in response to TLR ligand stimulation were associated with PTD but not SGA among women initiating ART in, but not before, pregnancy, suggesting immune anergy to microbial stimulation as a possible underlying mechanism for PTD in women initiating ART in pregnancy. Abstract : Here, we show that low immune cell activation and lowered cytokine production by monocytes in response to toll-like receptor ligand stimulation in early pregnancy in women initiating antiretroviral therapy in pregnancy is associated with preterm but not small-for-gestational age delivery.